The Impact of Javanesse Language to English Pronunciation Error: How and Why? - Rahmatika Kayyis; Ulfah Putri Intan Sari (Universitas Lancang Kuning, 2017)
The aim of this research is to investigate how and why Javanesse language has impact on to English Pronunciation Error? The design of the research was a case study in the form of qualitative research using the principle of contrastive analysis to analyze the data. The participants were chosen regarding to Javanese native speaker who learn English for the foreign language in semester three and five of English Education Department in STKIP Muhammadiyah Pringsewu Lampung. Recording pronunciation test and interview were used to collect the data. Phonetics transcription online were used to find the error and transcribe it into phonetics symbol. As the findings, this research focuses on 50% errors. Javanese committed errors on /d/, /b/, /p/, /g/, stressing words at the middle, last. Morever, their problem in long vowel, voiced consonant, stressing word at the first, middle, and last, and falling and rising intonation as the result of their Javanese language. Moreover, the error were also influenced by age. Despite of the impact of mother tongue to English pronunciation was strong enough. Some method and technique can be applied to reduce students‟ problem in pronouncing English words.